Comparison Between Dry Needling And Laser Combination Of Core Stability Exercise To Decrease Myogenic Low Back Pain Complaints - Saifudin Zuhri; Marti Rustanti (Poltekkes Kemenkes Surakarta, 2022)
Background: While performing daily activities, the incidence of myogenic low back pain (LBP) is experienced by many people. Physiotherapy technology in the form of dry needling and laser after both have received core stability exercise has not been widely applied in physiotherapy measures to reduce pain in complaints of myogenic low back pain. Therefore, further research is needed to compare the effectiveness of dry needling and laser with a combination of core stability exercises on low back pain myogenic complaints. Methods: Experimental study design with two groups of pre-test and post-test designs. The research was conducted in 2021 at Sunafa physiotherapy practice, Colomadu, Karanganyar. Subjects with myogenic low back pain complaints who met the study criteria. Analysis of the research data obtained, the data is not normally distributed, therefore tested with a non-parametric test, namely the Wilcoxon test and Mann-Whitney test. Results: Has the effect of dry needling with core stability exercise on pain reduction in myogenic low back pain complaints (p = 0,000), has the effect of a laser with core stability exercise on pain reduction pain in myogenic low back pain complaints (p = 0,000), there is a different effect between dry needling and core stability exercise and laser with core stability exercise to reduce pain in myogenic low back pain complaints (p = 0.002), dry needling with core stability exercise was more effective than laser with core stability exercise in reducing pain in myogenic low back pain complaints with a mean difference of 8.94 mm more significant in the group I. Conclusion: Dry needling is more effective than laser after both have undergone core stability exercise to relieve pain with myogenic low back pain complaints equations. So dry needling is preferable to laser in the treatment of myogenic low back pain.